Atmospheric and oceanic influence on mass balance of northern North Atlantic region land‐terminating glaciers. Issue 4 (17th July 2014) - Mernild, Sebastian H.; Hanna, Edward; Yde, Jacob C.; Seidenkrantz, Marit‐Solveig; Wilson, Ryan; Knudsen, Niels Tvis
Abstract In this study, observed annual mass‐balance data series from 1970 to 2009 for 29 land‐terminating glaciers and ice caps in the northern North Atlantic region are presented to highlight their spatio‐temporal variability. The glaciers and ice caps mass‐balance data are compared with various zonal latitude bands of regional near‐surface air temperature time series, large‐scale atmospheric and oceanic circulation indices, as well as with North Icelandic sea‐surface temperature records, since variations in mass‐balance conditions are related both to variations in surface weather conditions and to atmospheric and oceanic circulations. The purpose is to explore statistical and physical relations based on the hypothesis that the general atmospheric and sea‐surface warming trends are potential drivers of the ongoing regional glaciers and ice caps mass change. Our analysis shows that the mean observed northern North Atlantic glaciers and ice caps annual mass balance was mostly negative during the first decade of the twenty‐first century, with a variability in glaciers and ice caps loss from c. 860 mm water equivalent yr–1 for Southeast Greenland and Iceland to c. 380 mm water equivalent yr–1 for Svalbard and Scandinavia. For Iceland and Scandinavia, variations in the North Atlantic oscillation seem to be important for mass‐balance conditions, whereas overall for the entire northern North Atlantic region the mass‐balance time series was significantly correlated with both NASA's Goddard Institute for Space Studies regional near‐surface air temperature and Atlantic multidecadal oscillation time series, individually.